Implementing telehealth support to increase physical activity in girls and women with Rett syndrome—ActivRett: protocol for a waitlist randomised controlled trial - Nicholas Buckley; Helen Leonard; Cochavit Elefant; Kingsley Wong; Jenny Downs; Meir Lotan; Michelle Stahlhut (BMJ Open)
Introduction Individuals with Rett syndrome (RTT) experience impaired gross motor skills, limiting their capacity to engage in physical activities and participation in activities. There is limited evidence of the effectiveness of supported physical activity interventions. This study aims to evaluate the effects of a telehealth-delivered physical activity programme on physical activity, sedentary behaviour and quality of life in RTT.Methods and analysis This is a multicentre study, conducted in Australia, Denmark and Israel. It is a randomised waitlist-controlled trial comparing an intervention to support physical activity with usual care. Participants are children and adults with RTT, recruited from the Australian Rett Syndrome Database, the Danish Center for Rett Syndrome and the Rett Syndrome Association of Israel. The intervention duration is 12 weeks, including fortnightly telephone contact to plan, monitor and develop individual activity programmes. Outcomes are measured at baseline, at 13 weeks and then at 25 weeks. The primary outcomes are sedentary behaviour assessed with an activPAL accelerometer and the number of daily steps measured with a StepWatch Activity Monitor. Secondary outcomes include sleep, behaviour and quality of life. Caregiver experiences will be assessed immediately after the intervention using a satisfaction questionnaire. Group differences for each outcome will be evaluated with analysis of covariance, adjusting for baseline values on an intention-to-treat basis.Ethics and dissemination Ethics approval has been obtained in Western Australia from the Child and Adolescent Health Services (RGS3371), in Denmark from the Capital Region Ethics Committee (H-19040514) and in Israel from the Ariel University Institutional Review Board (AU-HEA-ML-20190331). Manuscripts on the development of the intervention from pilot work and the results of the intervention will be submitted to peer-reviewed journals. Results will be presented at conferences and consumer forums. We will develop an online resource documenting the physical activity programme and available supporting evidence.Trial registration number NCT04167059; Pre-results.